Prognostic Value of Various Diagnostic Methods for Long-Term Outcome of Newborns After Hypoxic-Ischemic Encephalopathy Treated With Hypothermia - Troha Gergeli, Anja; Škofljanec, Andreja; Neubauer, David; Paro Panjan, Darja; Kodrič, Jana; Osredkar, Damjan (Frontiers in Pediatrics, 2022)
ABSTRACT Introduction Prediction of outcome in newborns with hypoxic-ischemic encephalopathy (HIE) has been modulated by hypothermia treatment (HT). We assessed the predictive value of diagnostic methods commonly used in neonates with HIE for short-term neurodevelopmental outcome and long-term neurological outcome. Materials and Methods This longitudinal cohort study followed up 50 term newborns who underwent HT after HIE between July 2006 and August 2015, until preschool age. We estimated sensitivity and specificity for short-term neurodevelopmental outcome at 18 months and long-term neurological outcome at five years based on Amiel-Tison Neurological Assessment (ATNA), electroencephalography (EEG), and magnetic resonance imaging (MRI) performed in the neonatal period. Results The accuracy of all neonatal methods tested was higher for long-term neurological outcome compared to the predictive accuracy for short-term neurodevelopmental outcome at 18-24 months. Sensitivity and specificity in predicting unfavorable long-term neurological outcome were: MRI (sensitivity 1.0 [95%CI 0.96 - 1.0]; specificity 0.91 [95%CI 0.86 - 1.0]), EEG (sensitivity 0.94 [95%CI 0.71 - 1.0]; specificity 1.0 [95% CI 0.89 - 1.0]), and ATNA (sensitivity 0.94 [95%CI 0.71 - 1.0]; specificity 0.91 [95%CI 0.76 - 0.98]). Conclusion MRI is a powerful predictor of long-term neurological outcome when performed in the first week after HIE in HT treated infants, as are EEG and ATNA performed in the second or third week postnatally.